Peningkatan Kerja Sama dan Hasil Belajar Siswa Melalui Media Kartu Domino Timbangan - Al-Amin, Halija Putri; Imawan, Okky Riswandha; Pujowati, Maya (Media Pendidikan Matematika, 2026)
This research is motivated students of SD Negeri Perumnas 2 Waena who often play gaplek cards during recess. This shows that students have a high interest in card games and enjoy playing with friends. However, in mathematics learning on scales, student cooperation is still low and the learning outcomes of some students have not reached completeness. Therefore, learning is needed that utilizes student interests through group-based learning with the help of domino cards weighing media. This study aims to improve student cooperation and mathematics learning outcomes on scales. The method used is Classroom Action Research which is carried out in two cycles, namely planning, action implementation, observation, and reflection. The subjects of this study were 25 third-grade students of SD Negeri Perumnas 2 Waena. The instruments used were observation sheets to measure student cooperation and test sheets to measure learning outcomes. Success indicators are determined based on the Minimum Completion Criteria (KKM) of 70 for individual completeness and 70% for classical completeness. The results of the study showed that the percentage of student cooperation increased from 40% in the pre-action to 64% in cycle I and 92% in cycle II. Student learning outcomes also increased from 32% in the pre-action to 60% in cycle I and 96% in cycle II. Based on the results of the study, it can be concluded that group-based learning assisted by domino weighing cards can improve cooperation and mathematics learning outcomes of third-grade students of SD Negeri Perumnas 2 Waena on the material of weighing.